All Days 2014
DOI: 10.2118/169134-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Effect of Oil Saturation on the Optimum Acid Injection Rate in Carbonate Acidizing

Abstract: The existence of an optimum injection rate for wormhole propagation and face dissolution at low injection rates during matrix acidizing are well established. However, little has been documented that describes how the presence of residual oil affects carbonate acidizing. This study demonstrates the impact of oil saturation on wormholing characteristics while acidizing field and outcrop cores under reservoir conditions (200°F). Knowledge of the effect of different saturation conditions on acid performance will c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As a result, formation damage can occur. Therefore, core flow tests should be conducted to examine the potential formation damage problems during polymer flooding processes prior to field application [18,19]. The adsorption in polymer flooding can be severe, as it is irreversible and the adsorbed polymer occupies a large pore volume.…”
Section: Problems Associated With Polymer Floodingmentioning
confidence: 99%
“…As a result, formation damage can occur. Therefore, core flow tests should be conducted to examine the potential formation damage problems during polymer flooding processes prior to field application [18,19]. The adsorption in polymer flooding can be severe, as it is irreversible and the adsorbed polymer occupies a large pore volume.…”
Section: Problems Associated With Polymer Floodingmentioning
confidence: 99%
“…It is very challenging to achieve long lasting fracture conductivity in shale formation due to shale's mineralogy and mechanical properties, especially for soft, clay-rich shale formations. Prospective shale formation varies significantly in clay content and mechanical properties ( Table 2), therefore requires different hydraulic fracturing strategy [13][14][15][16]. The presence of rich clay content in shale formation can cause many potential formation damage problems, thus leading to fracture conductivity damage.…”
Section: Fracture Conductivity In Shale Formationmentioning
confidence: 99%
“…Researchers found that pH value of 10.5 is the optimum value where cross linker is most effective. Cross linkers are in equilibrium and can be broken by shear stress [18] (Table 1 and Figure 1). There are mainly three categories of breakers: oxidizer, acid and enzyme.…”
Section: Componentsmentioning
confidence: 99%